GENERATION Z AND THE TRANSFORMATION OF ONLINE PURCHASING: THE ROLE OF E-COMMERCE IN CONSUMER PREFERENCES - Stefani I. Angmalisang; Stanss L. H. V. Joyce Lapian, Silvya L. Mandey, Altje Lenny Tumbel, Willem J. F. Alfa Tumbuan (Adisam Publisher, 2024)
This research examines Generation Z consumers' preferences regarding online purchasing and the influence of e-commerce on their shopping patterns. Through analysis of online shopping behavior and consumer responses, this study provides insight into how brands can optimize the online shopping experience for Generation Z.